Interactive Learning of the Ukrainian Language Among Students Using AI-Based Chatbots - Boiko, Olha; Gevorkian, Norik; Vyshnevska, Galyna; Derevianko, Liudmyla; Gruba, Tamila (Journal of Vasyl Stefanyk Precarpathian National University, 2026)
The relevance of this study is driven by the growing need to integrate innovative digital tools, particularly artificial intelligence (AI)-based chatbots, into the educational process to enhance language learning efficiency and adapt to modern educational challenges. The work aimed to conduct a comprehensive evaluation of the effectiveness of integrating an AI chatbot into the process of learning the Ukrainian language, focusing on the development of language competencies and student motivation. The research was based on an experiment involving 96 students, divided into a control group (traditional methods) and an experimental group (using the chatbot). A mixed-method approach was employed: testing using the Attitude/Motivation Test Battery (AMTB), Natural Language Processing (NLP) metrics: BLEU (75%) and ROUGE-L (82%) to assess response quality, and in-depth analysis of interaction log files. Student's t-test was used for statistical data validation. The obtained results revealed a statistically significant advantage for the experimental group. Students in this group demonstrated higher response relevance (4.2 vs. 3.5 in the control group), as well as improved grammatical (76.4 vs. 62.3) and lexical competence scores (79.9 vs. 70.1). The motivation test also recorded substantial positive shifts: the average score for language interest was 4.5 (vs. 3.8), while the anxiety level significantly decreased to 2.0 (vs. 2.7). The scientific novelty of the research lies in the development and testing of a specialized AI-based chatbot for learning the Ukrainian language, built on a transformer architecture and the implementation of an integrated assessment approach that simultaneously encompasses technological efficiency (through NLP metrics and log-file analysis) and pedagogical-psychological impact (on motivation and anxiety). The results confirm that the integration of AI chatbots is an effective tool for enhancing motivation, academic achievement, language skills development, and anxiety reduction. Prospects for further research include analyzing the long-term impact and adapting the methodology to other disciplines and cultural contexts.